Citra Pemuda Muslim dalam Berita Jawa Pos Online: Analisis Linguistik Korpus - Dr. Zakiyah Arifa, M.Pd; Vita Nur Santi; Mafruhatun Nadifah (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
This study aims to capture the image of Muslim youth in the national media Jawa Pos online using corpus-based linguistic analysis. The tendency and alignment of the media in portraying Muslim youth can lead to positive, negative, and neutral public opinion. This research is a text study using a quantitative and qualitative descriptive approach, by collecting news with the keywords Muslim/Islamic youth on Jawapos online and obtaining 39 news stories with 12,636 words. The news text is then analyzed and applied using Antcont to obtain linguistic features of word frequency, collocation, and concordance with descriptive linguistic analysis. The research results show that; the frequency of words that are significant means that the Jawa Pos online in reporting on Muslim youth tends to be general, with the involvement of government activities in places of worship, namely masjid. The emergence of collocations tends to be more about reporting on mosque youth, although there is a tendency for political elements and implies messages and actions that must be carried out by youth. Whereas with the emergence of concordance, this media provides definitions to opinions about the meaning of Muslim youth in general, both negative, neutral, and positive, and more often generates news with a positive and balanced tendency. From this result, the Indonesian national media should report in a balanced manner in constructing the image of Muslim youth in Indonesia, where the majority of the population is Muslim.Keywords -  Corpus Analysis, Imaging, Muslim Youth, National Online Media.